Does Market Portfolio Index Really Affect Foreign Exchange Exposure? An Empirical Evidence from Malaysian Nonfinancial Firms (Global Business Management Review (GBMR), 2019)
Financial theory holds that fluctuations in exchange rate significantly influence open market firms by affecting their cash flows and firm value. Because of high market openness and fluctuations in Malaysian exchange rate, this study first investigates the extent to which 224 sampled firms of Malaysia face foreign exchange risk during the period of 2008 to 2014. It is found that 37% of the firms are exposed to (total) foreign exchange rate exposure during sample period. The dominance of Malaysian firms with positive Î²1 in each year implies that most of the Malaysian firms in the sample are net-exporters. To test the sensitivity of market portfolio index in exposure model, the Malaysian market index, i.e., FBMEMAS, is added in the exposure model and foreign exchange exposure for Malaysian firms is re-estimated over the sample period. It is obvious from the results that the number of significant coefficients of market index remains surprisingly high throughout the sample period than that of trade- weighted Index (TWI). A 67% of total firms have significant relationship with market index over the sample period as compared to 9% of TWI which shows drastic decreased in foreign exchange exposure by 76%. These results confirm that sometimes market portfolio index as a whole become strongly correlated with exchange rate changes and, in result, it dramatically reduces foreign exchange exposure.